A Phase 2 Randomized, Sham-Controlled Trial of Internal Carotid Artery Infusion of Autologous Bone Marrow–Derived ALD-401 Cells in Patients With Recent Stable Ischemic Stroke (RECOVER-Stroke). Issue 2 (8th January 2019) - Savitz, Sean I.; Yavagal, Dileep; Rappard, George; Likosky, William; Rutledge, Neal; Graffagnino, Carmelo; Alderazi, Yazan; Elder, Jennifer A.; Chen, Peng R.; Budzik, Ronald F.; Tarrel, Ronald; Huang, David Y.; et al.
Abstract : Background: Ischemic stroke has no approved treatments to enhance recovery. ALD-401 is an enriched population of aldehyde dehydrogenase-bright stem cells, capable of reducing neurological deficits in animal models. The primary objective of this trial was to determine the safety of internal carotid artery, intra-arterially delivered autologous bone marrow–derived ALD-401 in patients with disabling middle cerebral artery stroke in comparison with sham harvest with sham infusion. Secondary objectives were to determine feasibility and efficacy. Methods: This was a prospective phase 2, industry-funded, randomized, sham-controlled, parallel-group, multicenter study with blinded assessments. One hundred subjects were planned, aged 30 to 83 years, with confirmed first-time middle cerebral artery ischemic stroke with modified Rankin scale ≥3. Study patients were randomly assigned 3:2 to bone marrow harvest at 11 to 17 days after stroke followed 2 days later by intracarotid infusion of ALD-401 versus sham harvest and then sham infusion in the same timeframe. The primary study outcome was safety based on the incidence of a 4-point National Institutes of Health Stroke Scale worsening and the proportion of serious adverse events. Efficacy was based on modified Rankin scale change at 90 days. Other secondary outcomes were the proportions of patients experiencing adverse events, disability by Barthel Index, quality of life using EQ-5D, rehabilitation utilization, disability at 1 year, and MRI evidence of complications. Results: There were no infusional or allergic reactions and no difference in treatment emergent adverse events. Four patients had small areas of asymptomatic restricted diffusion on MRI in the treatment group. There was no significant difference between the ALD-401 and placebo groups on the modified Rankin scale for the intent-to-treat population at day 90 (mean difference, 0.3; 95% CI, –0.3 to 0.8; P =0.330). There were no significant differences between the groups on any of the secondary efficacy measures. Conclusions: Intracarotid infusion of ALD-401 does not lead to clinical adverse events in patients with subacute ischemic stroke, although there was a higher incidence of small lesions on MRI in the treatment group. There was no difference in the primary efficacy end point between the groups. The study provides a framework for the design and conduct of future intra-arterial cell therapy trials in stroke. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01273337. Abstract : Supplemental Digital Content is available in the text.